A brief procedure for big data analysis of gene expression. Issue 3 (25th September 2018) - Wang, Kewei; Wang, Wenji; Li, Mang
Abstract: There are a lot of biological and experimental data from genomics, proteomics, drug screening, medicinal chemistry, etc. A large amount of data must be analyzed by special methods of statistics, bioinformatics, and computer science. Big data analysis is an effective way to build scientific hypothesis and explore internal mechanism. Here, gene expression is taken as an example to illustrate the basic procedure of the big data analysis.